2014
DOI: 10.1093/cercor/bhu005
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Neural Differentiation Between Feedback Conditions After Bimanual Coordination Training with and without Augmented Visual Feedback

Abstract: It has been established that bimanual coordination with augmented feedback (FB) versus no augmented feedback (NFB) is associated with activity in different brain regions. It is unclear however, whether this distinction remains after practice comprising both these conditions. Functional magnetic resonance imaging was used in humans to compare visual FB versus NFB conditions for a bimanual tracking task, and their differential evolution across learning. Scanning occurred before (Pre) and after 2 weeks (Post) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
52
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 85 publications
5
52
2
Order By: Relevance
“…Various feedback techniques are available to support the acquisition of such coordination skills and to promote integration of the subtasks into a gestalt (Swinnen and Wenderoth, 2004). Training-induced bimanual skill improvement is associated with changes in neural activation as demonstrated by fMRI studies (Beets et al, 2014;Debaere et al, 2004b;Puttemans et al, 2005;Remy et al, 2008;Ronsse et al, 2011). Accordingly, studies using EEG/MEG techniques have identified a bimanual learning network that is modulated by practice-induced changes, including the bilateral SM1, SMA, PMd, PPC and cingulate motor area (Gerloff and Andres, 2002).…”
Section: Bimanual Learning and Neural Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…Various feedback techniques are available to support the acquisition of such coordination skills and to promote integration of the subtasks into a gestalt (Swinnen and Wenderoth, 2004). Training-induced bimanual skill improvement is associated with changes in neural activation as demonstrated by fMRI studies (Beets et al, 2014;Debaere et al, 2004b;Puttemans et al, 2005;Remy et al, 2008;Ronsse et al, 2011). Accordingly, studies using EEG/MEG techniques have identified a bimanual learning network that is modulated by practice-induced changes, including the bilateral SM1, SMA, PMd, PPC and cingulate motor area (Gerloff and Andres, 2002).…”
Section: Bimanual Learning and Neural Plasticitymentioning
confidence: 99%
“…Also, the few available polyrhythmic studies have not challenged task allocation assignments for each limb in relation to hand dominance so far, as the fast rhythm is always performed by the dominant hand. More recently, polyrhythmic movements whereby the nondominant hand performs the faster of the 2 rhythms, have been explored in an fMRI study (Beets et al, 2014).…”
Section: Future Researchmentioning
confidence: 99%
“…A recent functional magnetic resonance imaging (fMRI) study from our group revealed the involvement of prefrontal brain regions, including bilateral dorsolateral prefrontal cortex (DLPFC), in addition to M1, during a complex bimanual coordination task17. Left DLPFC activations were particularly evident during the planning phase when a visual cue informed the subject about the forthcoming required movement.…”
mentioning
confidence: 98%
“…During acquisition, encoding of information takes place and improves performance, while learning can only take place following consolidation32. For the acquisition phase, a previous fMRI study showed decreased activations in the bilateral DLPFC after five days of training of a bimanual movement task17, suggesting that DLPFC is primarily involved in the initial acquisition phase. Instead, there is evidence to suggest that the primary motor cortex (M1) is highly involved in both acquisition33 and consolidation34.…”
mentioning
confidence: 99%
See 1 more Smart Citation